2023
DOI: 10.3390/fermentation9050415
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fermentation Characteristics of Pine Needles (Pinus densiflora) as Feed Additive

Abstract: In this study, the fermentation characteristics of pine needles were investigated for the first time and the possibility of using them as plant-derived feed additives was confirmed. Four types of fermented pine needle were prepared: (1) natural fermentation (CON); (2) Lactobacillus plantarum SK4315 fermentation (LPF); (3) Saccharomyces cerevisiae SK3587 fermentation (SCF); and (4) co-culture fermentation (CCF). Fermentation lasted 48 h, and samples were taken at 4-h intervals until 12 h, then at 24 and 48 h. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…For example, when the pH of the environment drops with the presence of lactic acid, the undissociated lactic acid diffuses over the membrane, reducing the cytoplasmatic pH, DNA function, and structural protein expression of L. monocytogenes [122,123]. Hwang et al reported their increase during the fermentation of P. densiflora with Lactiplantibacillus plantarum and Saccharomyces cerevisiae, which is probably related (with other compounds released during the fermentation) to the anti-listeria activity observed in the same work [104]. In addition to organic acids, antimicrobial peptides can also be produced during the fermentation process.…”
Section: Anti-listeria Effect Of the Extracts Obtained From Fermented...mentioning
confidence: 81%
“…For example, when the pH of the environment drops with the presence of lactic acid, the undissociated lactic acid diffuses over the membrane, reducing the cytoplasmatic pH, DNA function, and structural protein expression of L. monocytogenes [122,123]. Hwang et al reported their increase during the fermentation of P. densiflora with Lactiplantibacillus plantarum and Saccharomyces cerevisiae, which is probably related (with other compounds released during the fermentation) to the anti-listeria activity observed in the same work [104]. In addition to organic acids, antimicrobial peptides can also be produced during the fermentation process.…”
Section: Anti-listeria Effect Of the Extracts Obtained From Fermented...mentioning
confidence: 81%
“…Previous research showed that fermenting Chinese chives ( Allium tuberosum ) with Lactobacillus plantarum enhanced their content of functional substances, including propanoic acid, kaempferol, isorhamnetin, quercetin, benzoylmesaconine, and saponins. This process notably boosted the chives’ capacity to suppress the avian influenza virus ( Hwang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study showed that PNF, PNS, and PNP all promoted growth performance in broilers, with PNF having the best effects, while PNP and PNS also had desirable effects and can thus be recommended as well. The fermentation of the pine needle mixture using L. plantarum and S. cerevisiae in this experiment has previously been shown to have good antimicrobial activity and antioxidant activity, part of the reason for this is that mixed fermentation of L. plantarum and S. cerevisiae better reduces ANFs in pine needles and increases the concentration of probiotics, enzymes and metabolites [ 17 ]. Moreover, using Bacillus subtilis with antimicrobial and antioxidant properties has been shown to improve the expression of antioxidant enzyme genes in broiler chickens and significantly improve their growth performance [ 18 ].…”
Section: Discussionmentioning
confidence: 99%